Psychosocial adjustment and quality of life in children undergoing screening in a specialist paediatric hypertrophic cardiomyopathy clinic. (8th September 2015) - Spanaki, Adriani; O'Curry, Sara; Winter-Beatty, Jasmine; Mead-Regan, Sarah; Hawkins, Kate; English, Jennifer; Head, Catherine; Ridout, Deborah; Tome-Esteban, Maria T.; Elliott, Perry; Kaski, Juan P.
Abstract: Objective: This study aimed to assess the psychological well-being and quality of life in children with hypertrophic cardiomyopathy and the potential psychosocial impact of screening. Methods: A total of 152 children (aged 3–18 years) attending a specialist paediatric hypertrophic cardiomyopathy clinic, and their parents completed the Generic Core Scales and Cardiac Module of the Paediatric Quality of Life Inventory (PedsQL) questionnaire as well as the Strengths and Difficulties Questionnaire; 21 patients (14%) had hypertrophic cardiomyopathy (group A); 23 children (15%) harboured hypertrophic cardiomyopathy-causing sarcomeric mutations with normal echocardiograms (group G); and 108 children (71%) had a family history of hypertrophic cardiomyopathy with normal investigations and attended for clinical cardiological screening (group S). Results: In group A, mean PedsQL TM total scores reported by children and parents were lower than those reported by unaffected children (p<0.001). There was no significant difference between unaffected and gene-positive patients. Mean Cardiac module PedsQL TM total scores by children and parents were lower in children with hypertrophic cardiomyopathy compared with unaffected patients [mean child-reported total score 86.4 in group S versus 72.3 in group A (p<0.001) and 80.2 in group G (p=0.25); mean parent-reported total score 91.6 in group S versus 71.4 in group A (p<0.001) and 87 in group G (p=0.4)]. There was no significant difference between group S and group G on any of the scales, or between the three groups of patients in the mean Strengths and Difficulties Questionnaire scores. Conclusions: Children with hypertrophic cardiomyopathy have a significantly reduced quality of life. Importantly, Quality-of-Life scores among unaffected children attending for screening were not different compared with scores from a normative UK population.